Topical Treatment of Colquhounia Root Relieves Skin Inflammation and Itch in Imiquimod-Induced Psoriasiform Dermatitis in Mice - Li, Fei; Han, Dan; Wang, Bo; Zhang, Wentao; Zhao, Yan; Xu, Jing; Meng, Liesu; Mou, Kuanhou; Lu, Shemin; Zhu, Wenhua; Zhou, Yan (Mediators of Inflammation, 2022)
Itch is one of the major clinical manifestations of psoriasis, which is closely related with neurogenic inflammation and difficult to control. Colquhounia Root (CR) is a Chinese herb exhibiting broad bioactivities on anti-inflammation. This study was designed to explore the antipsoriatic and anti-itch potential of CR and its underlying mechanisms. Mice in a model of imiquimod-induced psoriasiform dermatitis were treated topically with CR for 7 days, and the severity of skin lesions and itch was significantly ameliorated. CR reduced the inflammatory cell infiltration, as well as mast cells in skins. Particularly, the expression of inflammatory cytokines and chemokine including Il17a, Il22, and Ccl20 and itch-related molecules such as SP, CGRP, and NGF in lesions were decreased in diseased mice upon application with CR. The normal human epidermal keratinocytes were stimulated with the M5 cytokine cocktail, the mixture of IL-17A, IL-22, Oncostatin M, IL-1α, and TNF-α, and cell viability and mRNA expression levels of inflammatory factors and itch-related molecules were measured after being treated with CR. We found that CR inhibited both cell hyperproliferation and overexpression of inflammatory cytokines and itch-related molecules in vitro. Altogether, we conclude that CR relieves psoriatic lesions and itch via controlling immunological and neurogenic inflammation.